The Performance of Entik as Result Crossbreed of (Muscovy> - Roesdiyanto, Roesdiyanto; Purwantini, DD (ANIMAL PRODUCTION, 2001)
A research has been conducted to investigate the performance of entik as result crossbreed of muscovy and duck as a meat producer. The method using of this research was experimental method. As the base design was Randomized Completely Design with factorial design (2x3x3) that consisted of the first factor was sex (S) comprised : s1=male and s2=female. The second factor was feed from (P) comprised: p1=mush, p2=crumble and p3=Paste, whereas the third factor was slaughtering age (U) that comprised u1=six weeks and u2=eight weeks and u3=ten weeks. The investigated parameters were carcass weight, percentage of meat weight, meat weight of carcass. Result of the research obtained the lowest average of carcass weight for male entik aged 6.8 and 10 weeks respectively was 750.26 g, 1142.69 g, and the highest was 1024.93 g, 1336.08 g, and 760.40 g, 1098 g, 1180.26 g and the highest was 985.28 g, 1378.96 g and 1390.20 g. The lowest average parentage carcass for male entik respectively was 59.63%, 60.14%  and 61.76%; the highest was 57.17%, 61.02% and 67.86%. Whereas for the female  the lowest was 57.17%, 62.30%, and  61.02% and the highest was 68.99% ,67.59%, and 67.45 %. The average of meat carcass weight for the whole treatment was 733.99±158.23 g with range around 466.15 up to 956.42 g, and the highest average was reached by female entik aged eight weeks who was feeding by mash that was 916.95±39.36 g. The average of meat carcass weight was 64.57±1.35% with the range around 56.66 up to 73.60%. Result of  the analysis of variances showed that the interaction  factor between the sex, feed form ands slaughtering age affected no significantly (P>0.05) on the carcass weight, percentage of carcass weight, meat carcass weight and the percentage of carcass weight, meat carcass weight and the percentage of meat carcass weight and the percentage of meat carcass weight. Review for each treatment concludes that the sex factor highest effect just only for percentage of meat carcass weight (P<0.01), feed form factor had a high significant effect (P<0.01) on the carcass weight and the meat carcass weight, whereas the slaughtering age factor has a high significant effect linearly (P<0.05) on  the  percentage of carcass weight. This may concluded that the female entik  give the percentage of meat carcass weight more high then the male, feeding by mash form for entik which slaughtering eight weeks old increase the percentage of carcass weight and meat carcass weight. (Animal Production 3(1): 31-39 (2001)Key Words: Entik, crossbreed, muscovy, duck, artificial insemination (AI)